Maritime empires : British imperial maritime trade in the nineteenth century - Killingray, David; Lincoln, Margarette; Rigby, Nigel (The Boydell Press in association with the National Maritime Museum, 2004)
"These essays, product of a conference at the National Maritime Museum, London, are by internationally known scholars who provide a wide-ranging but comprehensive picture of the activities of maritime empire. The essays discuss a variety of maritime trades -- the brutal business of the transatlantic slave trade, Honduran mahogany shipped to Britain, the movement of horses across the vast reaches of Asia and the Indian Ocean, the impact of new technologies as Empire expanded in the nineteenth century, the sailors who manned the ships, the settlers who moved overseas, and the major ports of the Imperial world, plus the role of the Navy in hydrographic survey."--Jacket